JAJANAN SEHAT PADA ANAK SEKOLAH DASAR NEGERI 204 KOTA JAMBI - Rahmi Dwi Yant; Salvita Fitrianti; Miko Eka Putri (Jurnal Abdimas Kesehatan (JAK), 2019)
Children usually forget breakfast and choose to buy snacks at school. Children buy snacks according to their likes without thinking about the ingredients contained in them.       Many snacks that do not meet health requirements threaten the health of children throughout 2004 in 164 outbreaks of food poisoning in 25 provinces in 7,366 cases and 51 of them died. Counseling was conducted on December 8, 2018 in SD Negeri 204 Kota Jambi with a total of 31 participants. Outreach results can be obtained by students in grade 5 understanding what is meant by healthy snacks, the benefits of healthy snacks, and the impact of unhealthy snacks. The results of this counseling also introduce students to a sample menu of healthy snacks, a type of healthy food content whose nutritional value is needed for the growth of these students. Conclusion Class 5 students know healthy snacks, benefits and effects of unhealthy snacks, are expected for the next counseling activity to involve parents.